2016
DOI: 10.18632/oncotarget.8583
|View full text |Cite|
|
Sign up to set email alerts
|

Gap junction-mediated transfer of miR-145-5p from microvascular endothelial cells to colon cancer cells inhibits angiogenesis

Abstract: Gap junctional communication between cancer cells and blood capillary cells is crucial to tumor growth and invasion. Gap junctions may transfer microRNAs (miRs) among cells. Here, we explore the impact of such a transfer in co-culture assays, using the antitumor miR-145 as an example. The SW480 colon carcinoma cells form functional gap junction composed of connexin-43 (Cx43) with human microvascular endothelial cells (HMEC). When HMEC are loaded with miR-145-5p mimics, the miR-145 level drastically increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 43 publications
2
68
0
Order By: Relevance
“…More recently the long noncoding RNA metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) was found to regulate the expression of miR‐145‐5p, which in turn targeted AKAP12 . While these findings were made using prostate cancer cells, MALAT1, and miR‐145 are both known to affect endothelial cell migration and angiogenesis, especially in cells exposed to hypoxia and in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…More recently the long noncoding RNA metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) was found to regulate the expression of miR‐145‐5p, which in turn targeted AKAP12 . While these findings were made using prostate cancer cells, MALAT1, and miR‐145 are both known to affect endothelial cell migration and angiogenesis, especially in cells exposed to hypoxia and in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, astrocytes deliver miRNAs (eg, miR‐16, miR‐709) to cancer cells via a GJ‐dependent mechanism to suppress tumor cell growth . Similarly, the exchange of miR‐145 and miR‐5096 was found between endothelial cells and glioblastoma cells . Upon co‐culture with macrophages, the proliferative activity of hepato‐carcinoma cells was decreased, mediated by the delivery of miR‐142 and miR‐223 via GJs .…”
Section: Gap Junctional Shuttling Of Mirnamentioning
confidence: 99%
“…Previous studies demonstrated that miR‐145 functions as a tumor suppressor via inhibition of tumor angiogenesis in various cancers, including colon cancer, pancreatic cancer, and breast cancer . VEGF was an established downstream target of miR‐145 during regulation of tumor angiogenesis .…”
Section: Discussionmentioning
confidence: 99%